Eating Habits, Anxiety and Depression in Patients with Irritable Bowel Syndrome: Clinical and Laboratory Comparisons - O. V. Gaus; M. A. Livzan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to assess the level of stress hormones (cortisol in saliva), neurotransmitters (serotonin in blood serum, dopamine in blood plasma) in relation to eating habits, anxiety and depression levels in patients with IBS.Materials and methods. An open cohort prospective study was conducted with the inclusion of 263 patients with an established diagnosis of IBS, among them 189 (71.9 %) women and 74 (28.1 %) men. The average age of patients with IBS was 29 [25; 35] years. The control group included 40 healthy volunteers. All individuals included in the study were assessed for diet and eating habits using the WHO CINDI program questionnaire, “Information on Nutrition and Eating Behavior”, the severity of anxiety and depression according to the HADS questionnaire, the level of specific anxiety in relation to gastrointestinal symptoms according to the VSI questionnaire, quality of life according to the IBS-QoL questionnaire. In addition, the enzyme immunoassay method was used to assess the levels of cortisol in the morning and evening portions of saliva, serotonin in the blood serum and dopamine in the blood plasma.Results. Among patients with IBS there is a statistically significantly higher level of cortisol in the morning and evening portions of saliva (U = 19.5, p < 0.001 and U = 111.5, p < 0.001, respectively), serotonin in blood serum (U = 269.0, p = 0.042) and lower plasma dopamine levels (U = 93.5, p = 0.0002) compared with controls. The mean salivary cortisol level among patients with IBS was 45.39 [29.86; 70.10] ng/ml in the morning and 19.21 [13.98; 23.50] ng/ml in the evening, while in the group of healthy individuals it was 19.0 [16.5; 21.7] and 9.7 [8.5; 10.5] ng/ml, respectively. The average content of serotonin in blood serum in patients with IBS was 188.78 [150.41; 230.32] ng/ml, among healthy individuals — 142.80 [130.52; 154.15] ng/ml. The average content of dopamine in blood plasma in patients with IBS was 28.83 [20.08; 41.54] ng/ml, in healthy individuals — 58.20 [48.15; 66.62] ng/ml.Conclusion. In patients with IBS the secretion of the stress hormone (cortisol) and neurotransmitters (serotonin, dopamine) is closely related to the nature of nutrition, the level of anxiety and depression, and is also associated with the clinical variant and severity of the course of the disease.